Hematological and biochemical characteristics and diagnostic imaging results in acute T cell–mediated rejection after pediatric liver transplantation. (7th October 2021) - Osawa, Ichiro; Ide, Kentaro; Sakamoto, Seisuke; Uchida, Hajime; Fukuda, Akinari; Nishimura, Nao; Haga, Chizuko; Yoshioka, Takako; Nosaka, Shunsuke; Nakagawa, Satoshi; Kasahara, Mureo
Abstract: Background: Liver biopsy is the gold standard for diagnosing TCMR after LT. However, complications caused by liver biopsy may occur especially during the immediate post‐transplantation period and other effective methods for predicting TCMR have not been established. Thus, we investigated whether hematological and biochemical characteristics and Doppler ultrasonography findings are associated with acute TCMR. Methods: A multiple logistic regression analysis was performed to identify the prognostic factors of acute TCMR, defined as a RAI ≥4. Then, a ROC curve analysis was conducted to evaluate for diagnostic performance. The relationship between prognostic factors and each histological category of RAI was investigated. Results: Eighty‐nine liver biopsies were performed on 85 patients between January 2012 and December 2019. The RAI of 62 (69.7%) liver biopsies was ≥4. AEC (×10 4 /μl), direct bilirubin level (mg/dl), and MHVV (cm/s) were found to be associated with acute TCMR (OR: 4.96, 95% CI: 1.44–17.0, p  = .011; OR: 1.41, 95% CI: 1.04–1.91, p  = .025; OR: 1.05, 95% CI: 1.02–1.08, p  < .001, respectively). The area under the ROC curves for predicting acute TCMR was 0.86 (95% CI: 0.78–0.94). There was a correlation between AEC, direct bilirubin level, and MHVV as well as the severity of RAI. Conclusions: AEC, direct bilirubin level, and MHVV were the independent risk factors for acute TCMR. This study could provide information regarding the identification of patients requiring liver biopsy.